Niccolò Machiavelli: klasyczny realizm i republikanizm - Raburski, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Article presents life and ideas of Niccolò Machiavelli. Machiavelli is placed in the context of his times. His influence on the development of modern political thought is examined. The examples of his wider impact on western culture are given. Machiavelli is described as a founding father of two strands of political philosophy: political realism and republicanism.